Calycosin Enhances Some Chemotherapeutic Drugs Inhibition of Akt Signaling Pathway in Gastric Cells. (28th May 2017) - Zhou, Lixia; Wu, Yueming; Guo, Yang; Li, Yanjun; Li, Na; Yang, Yi; Qin, Xueyun
ABSTRACT: Although diagnosis and treatment of gastric cancer have improved, the prognosis of patients remains poor. The majority of patients should be treated with chemotherapy or other follow-up treatment. However, the drug resistance of chemotherapy and heterogeneity of tumor itself lead to differences of sensitivity of chemotherapy drugs for different patients. Therefore, it is mandatory to develop better methods of treatment for treatment of gastric cancer. Calycosin has been used in several types of cancer cells. Cisplatin, 5-fluorouracil (5-FU), and adriamycin (ADM) are most widely used drugs for chemotherapy, and they improve the overall survival of cancer patients. To study whether and how calycosin enhances their inhibition of gastric cancer cells, we detected the signaling pathway in which calycosin and cisplatin, 5-FU, and ADM play role in human gastric cells lines. We found that calycosin can enhance the suppression of cisplatin to gastric cell line by inhibiting the phosphorylation of protein kinase B (Akt). So, when cisplatin/5-FU/ADM is combined with calycosin, it can achieve better therapeutic effect in lower concentration.